Are school children using standing desks at risk of musculoskeletal discomfort? Evidence from a field study of school children - Parry, Sharon; Ee, Joyln; IR de Oloveira, Beatriz; Howie, Erin; McVeigh, Joanne; Straker, Leon (2018)
Background: The increased rate of tablet and computer use at school and during leisure time has meant that children are spending more time sedentary in undesirable postures, which is thought to be related to a high prevalence of musculoskeletal discomfort such as neck and back pain in children. (1, 2) As children spend a high proportion of their waking hours at school predominantly sitting (3), classroom based interventions provide an opportunity to change sedentary behaviours and potentially modify other health issues such as musculoskeletal discomfort. Aims: The aim of this study was to evaluate the impact of a standing desk intervention on children’s musculoskeletal discomfort, standing and sitting time at school and sedentary time and physical activity during waking hours. Methods: Male participants (47 boys, aged 10-11 years) from a single Independent boys’ school took part in a within-subjects crossover study. Participants were allocated either a standing desk or traditional seated desk for 21 days and then changed desks for an additional 21 days. Participants wore two accelerometers (thigh and hip mounted) to assess classroom sitting and standing time and physical activity and sedentary time during waking hours and twice daily musculoskeletal discomfort ratings were collected during the last seven days of each condition. Results: Students were less likely to report musculoskeletal discomfort in the neck, shoulder, elbows and lower back when using standing desks (OR 0.52-0.74). In addition, when students used standing desks, standing time was 21 minutes/school day greater (p<0.001) and sitting time was 24 minutes/school day lower (p=0.003) compared to sitting at traditional desks. There were no significant differences in overall sedentary time or physical activity during waking hours between the standing and sitting conditions. Conclusion: The use of standing desks significantly reduced sitting and discomfort and increased standing during school hours, although total waking sitting exposure did not change. The provision of standing desks in classrooms appears to be a feasible and practical way of reducing classroom sitting time. There may also be additional health benefits such as reducing the likelihood of developing musculoskeletal discomfort. With the increasing use of technology in the classroom and during leisure time it may become recommended practice to encourage standing while interacting with technology. Classroom standing desks have the potential to positively influence the health of children and develop good movement habits into adulthood.